Design and implementation of a java based virtual laboratory for data communication simulation - Obinna Okoyeigbo; Edevbie Agboje; Evioghene Omuabor; Uyi Aiyudubie Samson; Abidemi Orimogunje (Institute of Advanced Engineering and Science, 2020)
Students in this modern age find engineering courses taught in the university very abstract and difficult, and cannot relate theoretical calculations to real life scenarios. They consequently lose interest in their coursework and perform poorly in their grades. Simulation of classroom concepts with simulation software like MATLAB, were developed to facilitate learning experience. This paper involves the development of a virtual laboratory simulation package for teaching data communication concepts such as coding schemes, modulation and filtering. Unlike other simulation packages, no prior knowledge of computer programming is required for students to grasp these concepts.